Axial Dependence of Collagen–Induced Thrombus Formation in Flowing Non-Anticoagulated Human Blood - Roald, Helge E; Sakariassen, Kjell S (Thrombosis and Haemostasis, 1995)
Platelet thrombus formation on collagen fibrils is most pronounced at the upstream end of the surface, and it gradually decreases along the axis in parallel with the direction of the blood flow. This phenomenon, known as axial dependent platelet thrombus formation, is explained by the balance of the platelet supply to the surface and the consumption of platelets by growing thrombi.In the present study we have affected this balance by (A) inhibiting the growth of platelet thrombi by aspirin (ASA) or clopidogrel, and thus increasing the platelet concentration at the surface, and by (B) utilising blood from cigarette smokers, who have enhanced thrombus formation immediately after smoking, and thus decreasing the platelet concentration at the surface. Thrombus formation in non-anticoagulated blood was triggered by collagen fibrils positioned in a parallel-plate perfusion chamber at a wall shear rate of 2600 s_1which is characteristic for moderately stenosed arteries. Morphometrical assessment of thrombus formation was performed at axial positions of 1 and 13 mm downstream to the blood flow inlet at the collagen surface.Platelet-collagen adhesion and thrombus volume in blood from nonsmokers were decreased at the downstream location by 39% (p ≤0.0001) and by 60% (p ≤0.0001), respectively. However, increasing the platelet concentration at the surface by partially inhibiting the thrombus growth by ASA or clopidogrel, reduced substantially the axial decrease in platelet adhesion and thrombus volume. The largest reduction was observed with clopidogrel which was also the strongest inhibitor of the thrombus growth at both axial positions investigated. The corresponding figures in blood from smokers with enhanced thrombus formation were 38% (p ≤0.0001) and 72% (p ≤0.001). Thus, enhanced upstream platelet consumption increased the axial reduction in thrombus volume, but not in platelet adhesion.These data substantiate the view that the “axial dependence phenomenon” may be explained by the balance between the platelet supply to the surface and the consumption of platelets by growing thrombi. It is also apparent that clopidogrel is a more potent inhibitor of platelet thrombus formation than ASA.